1993
DOI: 10.1590/s0074-02761993000400014
|View full text |Cite
|
Sign up to set email alerts
|

Climatic change in northeastern Brazil: paleoparasitological data

Abstract: Trichuris eggs were observed in Kerodon rupestris coprolites dated 9,000 years before present, collected in archeological sites of São Raimundo Nonato, northeastern Brazil. However, present day local rodents seem not to be infected by the parasite, suggesting its disappearence due to climatic changes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…Reports of Trichuris spp in South American rodents from ancient material are those of Ferreira et al (1991), Araújo et al (1993), Fugassa (2006) and Sardella and Fugassa (2009a, b), among others. Because of the overlap in the egg dimensions for Trichuris spp infecting rodents, not only in Argentina, but also in Chile, as is the case for Trichuris bradleyi, Trichuris chilensis, Trichuris fulvi and Trichuris robusti (Babero et al 1975, 1976, Babero & Murúa 1987, the parasites found in ADG were, therefore, assigned to more than one species of Trichuris.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of Trichuris spp in South American rodents from ancient material are those of Ferreira et al (1991), Araújo et al (1993), Fugassa (2006) and Sardella and Fugassa (2009a, b), among others. Because of the overlap in the egg dimensions for Trichuris spp infecting rodents, not only in Argentina, but also in Chile, as is the case for Trichuris bradleyi, Trichuris chilensis, Trichuris fulvi and Trichuris robusti (Babero et al 1975, 1976, Babero & Murúa 1987, the parasites found in ADG were, therefore, assigned to more than one species of Trichuris.…”
Section: Discussionmentioning
confidence: 99%
“…A estrutura da fauna helmíntica diferiu da citada no catálogo de Vicente et al (1997) (Araújo et al, 1993). Neste estudo, P. uncinata apresentou uma prevalência de 31,3% e variação de intensidade de 1 a 6 helmintos, valores próximos aos encontrados por Dittmar (2002) quando trabalhou com Cavia aperea (Caviidae), procedentes do Peru, nas quais encontrou uma prevalência de 37% e variação de intensidade de 0 a 7 helmintos.…”
Section: Discussionunclassified
“…A presença do gênero Trichuris no mocó, nos dias atuais, é de suma importância em razão dos ovos desse parasito só terem sido encontrados em material arqueológico de Kerodon rupestris até 2000 anos AP (Araújo et al, 1993;Duarte, 1994;Ferreira et al, 1991) e, desde então, não mais encontrados, sugerindo o desaparecimento deste gênero devido as alterações climáticas ocorridas na região Nordeste há 10000 anos, as quais originaram a formação semi-árida existente na atualidade. Posteriormente, em Pernambuco, foram diagnosticados ovos de Trichuris sp., datados de 2000 anos, permitindo aventar a possibilidade de manutenção do ciclo biológico naquela região, onde as condições climáticas, em contraste com outras regiões, não sofreram alterações tão intensas, constituindo paisagem de exceção dentro do domínio semi-árido do Nordeste.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Paleocoprology, or the study of coprolites, also yields precious data on the ancient demography of a given site, since it is possible to extract specifically male and female steroids from coprolites, in addition to mitochondrial DNA (mtDNA), used for taxonomic studies and studies on kinship and evolution (Sobolik et al, 1996). Paleoparasitology, a science that works closely with coprology, also produces information on parasitic diseases and possible migratory routes travelled by ancient human and animal populations (Araújo et al, 1988;Araújo, Rangel & Ferreira, 1993;Ferrreira et al, 1987).…”
Section: Preservation Of Pollenmentioning
confidence: 99%